How do surgeons make intraoperative decisions?. Issue 3 (1st June 2007) - Flin, Rhona; Youngson, George; Yule, Steven
Abstract : Surgeons' intraoperative decision making is a key element of clinical practice, yet has received scant attention in the surgical literature. In recent years, serial changes in the configuration of surgical training in the UK have reduced the time spent by trainees in the operating theatre. The opportunity to replace this lost experience with active teaching of decision making is important, but there seem to have been very few studies that have directly examined the cognitive skills underlying surgical decision making during operations. From the available evidence in surgery, and drawing from research in other safety-critical occupations, four decision-making strategies that surgeons may use are discussed: intuitive (recognition-primed), rule based, option comparison and creative. Surgeons' decision-making processes should be studied to provide a better evidence base for the training of cognitive skills for the intraoperative environment.